Description of the preimaginal stages of three species of the genus Tropisternus Solier, subgenus Strepitornus Hansen (Coleoptera: Hydrophilidae), with emphasis on morphometry and chaetotaxy - Torres, Patricia L. M.; Michat, Mariano C.; Archangelsky, Miguel (Zootaxa, 2008)
The morphology of immature stages of the genus Tropisternus Solier is investigated on the basis of the description of immatures of the subgenus Strepitornus Hansen. The egg cases, all three larval instars and pupae of T. collaris (Fabricius), T. parananus Sharp and T. scutellaris Castelnau are described with an emphasis on the chaetotaxy and morphometry of selected structures. Comparisons with other species of Tropisternus known as larvae are included. The larval instars can be separated by means of morphometric relationships and chaetotaxy of the cephalic appendages and legs. Most morphometric measures among the species described here have overlapped ranges, suggesting that the larval morphology of the examined taxa is very similar.